2022
DOI: 10.1155/2022/6255012
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ezrin in Asthma-Related Airway Inflammation and Remodeling

Abstract: Ezrin is an actin binding protein connecting the cell membrane and the cytoskeleton, which is crucial to maintaining cell morphology, intercellular adhesion, and cytoskeleton remodeling. Asthma involves dysfunction of inflammatory cells, cytokines, and airway structural cells. Recent studies have shown that ezrin, whose function is affected by extensive phosphorylation and protein interactions, is closely associated with asthma, may be a therapeutic target for asthma treatment. In this review, we summarize stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 127 publications
(160 reference statements)
0
0
0
Order By: Relevance
“…Zhao et al. 36 showed that the Ezrin phosphorylation limited the production of IL‐10 in B cells. Shan et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao et al. 36 showed that the Ezrin phosphorylation limited the production of IL‐10 in B cells. Shan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al 35 found that Ezrin promoted the generation of inflammatory factors TNFα, IL-1β and HMGB1. Zhao et al 36 showed that the Ezrin phosphorylation limited the production of IL-10 in B cells. Shan et al 37 believed that the cytoskeleton interaction mediated the mitochondrial dynamics and localization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though ezrin has been mostly discussed for its involvement in cancer [167], it is not known if ezrin could compensate for moesin should the latter be absent or "incapacitated" in mast cells. In fact, ezrin, has been implicated in asthma [168]. The phosphorylation of ezrin at Thr567 was associated with trophoblast motility [169].…”
Section: Moesin In Mast Cellsmentioning
confidence: 99%